2015
DOI: 10.1039/c5ra05803a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a pH responsive DOX conjugated PEGylated palladium nanoparticle mediated drug delivery system: an in vitro and in vivo evaluation

Abstract: Schematic illustration of the possible mechanism of pH based drug delivery system of DOX conjugated PEGylated PdNPs induced apoptosis in HeLa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 69 publications
4
40
0
Order By: Relevance
“…Herein, the DOX conjugation was proved with the decrease of fluorescence intensity and absorption peaks which was caused by the conjugation steps. In the other studies, similar cases showed up as demonstrated in Du et al 34 and Shantni et al 35 mV and -22.7±12 mV, respectively. Expectedly, the hydrodynamic particle size of AuNP-PMAA was increased after the DOX conjugation.…”
Section: Characterizationsupporting
confidence: 79%
“…Herein, the DOX conjugation was proved with the decrease of fluorescence intensity and absorption peaks which was caused by the conjugation steps. In the other studies, similar cases showed up as demonstrated in Du et al 34 and Shantni et al 35 mV and -22.7±12 mV, respectively. Expectedly, the hydrodynamic particle size of AuNP-PMAA was increased after the DOX conjugation.…”
Section: Characterizationsupporting
confidence: 79%
“…This notable correlation, together with the aforementioned experimental evidence indicates that the silica based nanocarriers are not only structurally fit to carry the cisplatin but also carry the phytochemical, β sitosterol to augment the anticancer activity against lung cancer, breast cancer . The similar result observed in the previous literature …”
Section: Resultsmentioning
confidence: 89%
“…While in apoptotic cells, an apoptotic body undergoes nuclear shrinkage and blebbing and as a result, these apoptotic cells were observed as orange colored bodies. Whereas, the loss of membrane integrity in necrotic cells showed red color fluorescence when viewed under fluorescence microscope (Figure c,d and e,f) …”
Section: Resultsmentioning
confidence: 96%